Fabrication of mono and dual layered zinc oxide nanorod array-based humidity sensors / Ahmad Syakirin Ismail@Rosdi - Ismail@Rosdi, Ahmad Syakirin (2016)
Humidity sensors have been fabricated using undoped, iron (Fe)- and tin (Sn)-doped zinc oxide (ZnO) nanorod arrays, and dual layered Sn-doped ZnO/SnC>2 core-shell nanorod arrays. These nanorod arrays were deposited on aluminum (Al)-doped ZnO seed layer-coated glass substrate. The nanorod array properties and the fabricated humidity sensor performances were analysed using field emission scanning electron microscopy (FESEM), transmission electron microscopy (TEM), X-ray diffraction (XRD) measurement, ultraviolet-visible-near-infrared (UV-vis-NIR) spectrophotometer, two-point probe current-voltage (I-V) measurement, and humidity sensor measurement system. In this study, several parameters were studied regarding the growth of ZnO nanorod arrays for humidity sensor application, including different doping elements (Fe and Sn), different Sn concentrations, different immersion times and different Sn02 coating times. Based on this analysis, it can be concluded that the performance of the humidity sensor was closely related to the impurities, nanorod dimensions (i.e., the diameter and length), crystallinity, and surface condition. In addition, Fe- and Sn-doped ZnO nanorod array-based humidity sensor were successfully fabricated using immersion method. Based on the sensor performance, both doped samples have good response to humidity. However, Sn-doped ZnO nanorod array-based humidity sensor possesses superior sensitivity to humidity. The optimisation on concentration of the Sn-doping was conducted. Sn-doped ZnO nanorod array-based humidity sensor at 1.0 mM Sn concentration produced the best sensitivity to humidity of 3.04 compared to other samples. Furthermore, the study on immersion time was also conducted. Sn-doped ZnO nanorod array-based humidity sensor immersed for 60 min was observed to produce the best sensitivity to humidity with the sensitivity of 3.92. It is concluded that fabrication of ZnO nanorod arrays using 1.0 mM Sn concentration at 60 min immersion time able to produce the best humidity sensor. Furthermore, surface decoration to the ZnO nanorods surface was also conducted by coating with Sn02 using immersion method. The decorated nanorod arrays possessed rough surface and high porous. The humidity sensitivity of dual layered Sn-doped ZnO/Sn02 core-shell nanorod array-based humidity sensor immersed for 3 min was observed to increase up to 5.29. Throughout this study, it was found that the performance of the fabricated ZnO nanorod arrays-based humidity sensor, particularly developed with the aligned Sn-doped ZnO nanorod arrays and dual layered Sn-doped ZnO/Sn02 core-shell nanorod arrays, displayed very promising and good sensitivity to humidity.